2020
DOI: 10.1111/evj.13295
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone exposure in utero did not affect articular cartilage of resulting foals

Abstract: Background: Recent studies have shown that fluoroquinolones, specifically, enrofloxacin and its active metabolite (ciprofloxacin), cross the equine placenta without causing gross or histological lesions in the first and third trimester fetuses or resulting foal. However, it is possible that in utero exposure to fluoroquinolones may cause subtle lesions not detectable by standard means; thus, a more in-depth assessment of potential toxicity is warranted. Objectives: To use quantitative magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For example, ciprofloxacin significantly reduced the hydrophobicity index of the bile acid pool of male Wistar rats, reduced secondary bile acids, and increased taurine-conjugated primary bile acids in both the serum and large intestine compared with moxifloxacin [ 88 ]. Severe cartilage erosions, synovitis, and joint capsular thickening were identified in foals postnatally treated with enrofloxacin, indicating that in utero exposure to FQs may cause subtle lesions [ 89 ]. Tang et al (2017) found that FQ antibiotics were enriched in the dorsal-epaxial muscle of living puffer fish, thus causing health risks for humans [ 90 ].…”
Section: Toxicity Effect Of Fq Antibiotics On Organismsmentioning
confidence: 99%
“…For example, ciprofloxacin significantly reduced the hydrophobicity index of the bile acid pool of male Wistar rats, reduced secondary bile acids, and increased taurine-conjugated primary bile acids in both the serum and large intestine compared with moxifloxacin [ 88 ]. Severe cartilage erosions, synovitis, and joint capsular thickening were identified in foals postnatally treated with enrofloxacin, indicating that in utero exposure to FQs may cause subtle lesions [ 89 ]. Tang et al (2017) found that FQ antibiotics were enriched in the dorsal-epaxial muscle of living puffer fish, thus causing health risks for humans [ 90 ].…”
Section: Toxicity Effect Of Fq Antibiotics On Organismsmentioning
confidence: 99%
“…For example, cipro oxacin signi cantly reduced the hydrophobicity index of the bile acid pool of male Wistar rats, reduced secondary bile acids, and increased taurine-conjugated primary bile acids in both the serum and large intestine compared with moxi oxacin(Wang et al 2020). Severe cartilage erosions, synovitis and joint capsular thickening were identi ed in foals treated with enro oxacin postnatally, indicating that utero exposure to FQs may cause subtle lesions(Ellerbrock et al 2020). Li et al (2018) found that a 125 mg/kg dose of enro oxacin induced catalase and glutathione peroxidase and increased CYP450 content in pig liver microsomes.Twenty-ve and 125 mg/kg doses of enro oxacin elevated the activity of microsomal NADPHcytochrome C reductase Tang et al (2017).…”
mentioning
confidence: 99%